Psycho-emotional conditions of patients with non-cicatrazing alopecia (circumsribed, androgenetic) - A. N. Mareeva; I. N. Kondrakhina (Vestnik Dermatologii i Venerologii, 2017)
Most common psycho-emotional disorders are described with patients with circumsribed, androgenetic alopecia. Main identification methods presented. It was shown based on analysis of literary data and in order to upgrade the quality of medical help for this group of patients how important it is to identify the preoccupying, depressive and other pathological psychogenic conditions of patients chronic alopecia.